2015
DOI: 10.14480/jm.2015.13.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Varietal characteristics of cross-bred Cordyceps militaris 'Dowonhongcho'

Abstract: Cordyceps militaris is being studied and cultivated as a medicinal mushroom having many valuable biological and pharmaceutical activities. In the breeding of new C. militaris mushroom, single ascospores were isolated and examined their mycelial growth, mycelial density, and production of stroma and perithecia. Among them selected isolates were crossed and hybrids were produced showing high quality fruiting bodies on artificial media. Mycelial growth rate of new strain 'Dowonhongcho' was higher than that of bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…The ash and fat content are insignificant, accounting for 1.43% and 1.41%, respectively. This result is slightly different from the composition of the sample of Cordyceps reported by Byung-joo Lee et al [20] with the corresponding components of moisture 86.26%, protein 5.03%, lipid 0.12%, carbohydrate 7.77% and ash 0.82%. The difference in the composition of substances in these samples of CM may be due to differences in origin, conditions, and cultivation methods.…”
Section: Composition Of Cordyceps Militariscontrasting
confidence: 92%
“…The ash and fat content are insignificant, accounting for 1.43% and 1.41%, respectively. This result is slightly different from the composition of the sample of Cordyceps reported by Byung-joo Lee et al [20] with the corresponding components of moisture 86.26%, protein 5.03%, lipid 0.12%, carbohydrate 7.77% and ash 0.82%. The difference in the composition of substances in these samples of CM may be due to differences in origin, conditions, and cultivation methods.…”
Section: Composition Of Cordyceps Militariscontrasting
confidence: 92%
“…All five strains investigated in this study showed the ability to form and develop primordia to the maturity stage. According to Lee et al (2015), the fruiting bodies of strain Dowonhongcho and strain Yedang 3 were formed on 15 days after inoculation. Under favorable conditions, the period for substrate colonization, primordia formation, and harvest of C. militaris were 5-6 days, 12 days, and 45-50 days after inoculation, respectively (Du et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps militaris (CM) is a species of fungus in the family Cordycipitaceae and the type species of the genus Cordyceps [1]. Its fruitbody is orange, (5÷8) cm long, D = (3÷5) mm in diameter The main components in the fruit body contain protein, moisture, ash, fat, and carbohydrates with different ratios depending on the type of CM [2][3][4]. CM is used as a functional food to prevent and treat some fatal diseases because it contains many vitamins and amino acids such as adenosine, cordycepin, and many other rare active ingredients [1,5].…”
Section: Introductionmentioning
confidence: 99%